Female single parents and family responsibilities: implications for social welfare (2020)
The study examined female single parents and family responsibilities in Ibadan. Three research objectives and questions were raised for the study. Research design adopted was descriptive based on case study approach. The population of this study consisted of all female single parents who are informal business owners trading in major markets in Ibadan aged 25 to 50 years. The sample was drawn using the purposive sampling technique to select five (5) respondents each from New Gbagi, Oje, Bodija, Aleshinloye, and Agbeni-Ogunpa markets making a total of 25 (twenty-five). The instrument used was a questionnaire to collect information on the biodata of respondents and in identifying those who are single parents with the criteria: as a result of divorce, death of husband (widow) and having children outside marriage. In-depth interview (IDI) was also used to collect information on the themes derived from the research questions raised for the study. The frequency counts and percentages were used to analyse the bio-data, while the thematic content analysis was used for the qualitative data. The study revealed that female single parents played dual roles and responsibilities such as feeding, clothing, medical, paying tuition fees amongst others. Single mothers faced different types of stress particularly decision making as regards welfare of the children, daily chores, child care and domestic duty and health. They adopted various coping strategies like spending more time with their children during weekends, getting more involved in household chores, watching television and listening to radio programme as well as engage in religious activities like prayer and fasting. The study recommended that social support in form of food, clothing, housing, counselling and emotional support could be provided to single parents to enable them care for their children and assist them in coping with their levels of stress